Satuan lingual pengungkap kearifan lokal dalam pelestarian lingkungan - Mardikantoro, Hari Bakti (citeus, 2016)
This study aims to reveal the type and the function of linguistic units as the proof of the local wisdom in preserving environment towards society of Javanese Talk. The data on the study are gathered and analyzed based on two procedures; they are the analysis on the process of collecting data and the analysis after the data are collected. The result of the study shows that the type of linguistic units consist of word, phrase, sentence, and expression. Meanwhile, those linguistic units function in expressing local wisdom such as in giving name, commanding/advising, praying, and teaching sesorah values.